1999
DOI: 10.1074/jbc.274.20.14204
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Murine A1 Adenosine Receptor Promoter, Potent Regulation by GATA-4 and Nkx2.5

Abstract: Adenosine acts via A1 adenosine receptors (A1ARs) in the heart and brain to potently influence mammalian physiology. A1ARs are expressed very early in embryonic development, and A1ARs are among the earliest expressed G protein coupled receptors in the heart and brain. To understand the biologic basis of A1AR expression, a genomic fragment containing the murine A1AR promoter was cloned. Reporter assay studies using DDT1 MF2 cells that express A1ARs revealed that 500 base pairs of the proximal A1AR promoter cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 32 publications
(48 reference statements)
0
21
0
Order By: Relevance
“…For the reporter gene assay, 1ϫ10 5 (TM3 and TM4 cells) or 2ϫ10 5 (P19.CL6 cells) cells were seeded into 2 ml medium containing 7% (v/v) FBS in each well of a 6-well culture plate, and then cultured for 24 h. 53) Lipofectamine · (Invitrogen) was used for transfection (duplicate) of plasmid DNA [reporter plasmid (0.5 mg) and pSV-b-Gal (0.5 mg) per well], according to the manual supplied by the manufacturer, except that the volume was quadrupled. Lysis buffer (90 ml) (Promega) was added to the phosphate-buffered saline [10 mM sodium phosphate buffer (pH 7.2), 137 mM NaCl, 3 mM KCl] (PBS)-washed plate 48 h after the start of transfection, and a cell lysate was prepared (12000ϫg, 10 min at 4°C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the reporter gene assay, 1ϫ10 5 (TM3 and TM4 cells) or 2ϫ10 5 (P19.CL6 cells) cells were seeded into 2 ml medium containing 7% (v/v) FBS in each well of a 6-well culture plate, and then cultured for 24 h. 53) Lipofectamine · (Invitrogen) was used for transfection (duplicate) of plasmid DNA [reporter plasmid (0.5 mg) and pSV-b-Gal (0.5 mg) per well], according to the manual supplied by the manufacturer, except that the volume was quadrupled. Lysis buffer (90 ml) (Promega) was added to the phosphate-buffered saline [10 mM sodium phosphate buffer (pH 7.2), 137 mM NaCl, 3 mM KCl] (PBS)-washed plate 48 h after the start of transfection, and a cell lysate was prepared (12000ϫg, 10 min at 4°C).…”
Section: Methodsmentioning
confidence: 99%
“…Since knockout mice exhibited specification of the cardiac cell lineage, 3,4) and ES cells with homozygous GATA-4(Ϫ/Ϫ) contributed to the heart tissue in chimeric embryos, 3) GATA-4 in procardiomyocytes or visceral endoderm cells likely regulate the expression of a morphogenic signaling molecule(s) that directs the migration of procardiomyocytes. Although GATA-4 knockout mice express cardiac contractile proteins, 3,4) a number of studies have suggested that both structural and regulatory genes in the cardiac muscle cells are targets of GATA-4, such as those of A1 adenosine receptor, 5) angiotensin II type Ia receptor, 6) atrial natriuretic peptide, 7) brain natriuretic peptide, [7][8][9] cardiac a actin, 10) cardiac troponin C, 11) cardiac troponin I, 9) cardiac-restricted ankyrin repeat protein, 12) amyosin heavy-chain, 9,13) b-myosin heavy-chain, 9) myosin light chain 1/3, 14) Na ϩ /Ca 2ϩ exchanger 1, 15,16) Nkx-2.5, 17,18) slow myosin heavy chain, 19) and corin. 20) It is also evident that GATA-4 functions in the regulation of both epithelial cell differentiation and gene expression in the gut 21,22) and gonads [23][24][25][26][27] in addition to the heart.…”
mentioning
confidence: 99%
“…117,118 The expression of several cardiac genes in the heart of Csx/Nkx2-5-deficient embryos (including MLC2v, ANP, BNP, CARP, MEF2-C, eHAND/HAND1, N-myc, Iroquois homeobox gene 4, and HOP) was reduced. [117][118][119][120][121][122] In addition, direct downstream targets for Csx/ Nkx2-5 (such as ANP, 52,123 cardiac ␣-actin, 124 A 1 adenosine receptor, 125 calreticulin, 126 connexin40, 127 and NCX1) have been identified. 128 These results indicate a functional role of Csx/Nkx2-5 in the transcriptional regulation of a cardiac gene program.…”
Section: Cardiac Homeobox Transcriptionmentioning
confidence: 99%
“…Embryonic cardiac A 1 AR expression appears to be driven by the transcription factors GATA4 and Nkx2.5, which are expressed in the heart during early embryogenesis (12). As soon as the heart begins to beat, A 1 ARs regulate embryonic heart rate, and adenosine is the dominant prenatal humoral regulator of the fetal heart rate (13).…”
mentioning
confidence: 99%